Processing of porous alumina by foaming method-effect of foaming agent, solid loading and binder. Issue 9 (15th June 2019) - Devavarapu, Soumya; Chaudhuri, Paritosh; Shrivastava, Aroh; Bhattacharyya, Santanu
Abstract: Porous Alumina ceramics were fabricated by foaming method using shikakai (Acacia Concinna) as a natural foaming agent in varying percentages (5, 10, 15 and 20 vol%) of the total liquid content in the slurry. The effect of two different binders (Guar Gum and PVA) and different solid loading (25, 30 and 35 vol%) as well as varying shikakai content on porosity development, strength and microstructure were studied. The slurry was gel cast in a plastic cup and was dried under humid condition at 60 °C followed by sintering at 1500 °C. It was observed that for every solid loading, an optimum amount of shikakai content is required for obtaining a porous cast with high open porosity. The slurry viscosity increased both with increasing solid loading and as well as the shikakai content. The maximum porosity (60.6 ± 0.5%) was obtained with PVA based binder system for 25 vol% solid loading sample at 15% shikakai content. It was also observed that with either binder, a range of slurry composition produced nearly equal porosity. The pore interconnections and the pore size distribution was dependent on solid loading as well as the binder. The compressive strength variation correlated well with the largest pore size of the samples. The strength data could also be fitted with Gibson- Ashby model.